Enhancement of Organizational Culture and Employee Performance Through Employee Engagement and Organizational Citizenship Behavior - Dina Prasetyaningrum (Universitas Pendidikan Ganesha, 2023)
This study aims to investigate the influence of employee engagement and organizational citizenship behavior on organizational culture and employee performance in the production division of PT. Wahana Kasih Mulia Kedungreja Cilacap. The problem behind this study is the importance of understanding the factors that influence organizational culture and employee performance in the context of the company's production division. The type of research used is quantitative research. The research sample consisted of 98 employees of the production division of PT. Wahana Kasih Mulia Kedungreja surveyed. The method of data collection used is the distribution of questionnaires to respondents, who are employees of the company's production division. Data analysis is carried out using statistical methods. The results showed that organizational citizenship behavior and employee engagement had a significant influence on organizational culture and employee performance in the production division of PT. Wahana Kasih Mulia Kedungreja. The conclusion of this study is that these factors play an important role in shaping a positive organizational culture and improving employee performance. The implication of this finding is the need for companies to manage employee engagement and organizational citizenship behavior effectively to improve organizational culture and employee performance in the production division.